The afterlife of sympathy : reading American literary realism in the wake of "Uncle Tom's Cabin" - Halpern, Faye (University of Massachusetts Press, 2024)
"Literary realism rose to prominence in postbellum America with bold and accurate depictions of the world. This style became more popular than sentimentality--an earlier form of writing often associated with women readers and high emotions, seemingly antithetical to realism. Literary scholar Faye Halpern challenges this apparent binary, finding elements of the sentimental in key realist texts. With a distinctively formal and narratological approach, The Afterlife of Sympathy reveals that realist writers such as William Dean Howells, Mark Twain, Henry James, Constance Fenimore Woolson, and Charles Chesnutt used sentimental techniques to evoke sympathy and readerly immersion, even though these techniques countered prevailing conventions of realism. By reassessing the literary realism of this era, Halpern seeks to not only understand why these writers adopted sentimentality's strategies but also provide insight into contemporary arguments about critical distance and sympathetic identification in reading"--